2003
DOI: 10.2174/1381612033454243
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Pseudoallergic Reactions Induced by Glucocorticoids: A Review

Abstract: Glucocorticoids (GCs) represent the most effective treatment for autoimmune and allergic diseases, even if collateral effects are not rare, especially endocrine and immunosuppressive manifestations. Moreover, these drugs can develop adverse immunological reactions of I, III or IV type. Though immediate adverse reactions caused by systemic therapy with GCs are not very frequent, the possible beginning of anaphylactic and pseudo-anaphylactic manifestations in patients undergoing therapy with these drugs has to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…In fact, patients allergic to the GCs of group A (hydrocortisone and methylprednisolone) tolerate the GCs of group C (betamethasone, dexamethasone, paramethasone). Patients with immediatetype reactions to intravenous succinate esters of hydrocortisone and methylprednisolone tolerate prednisolone (a GC of group A) orally, as reported by many authors [23,24,65,66]. This is probably due to the fact that the introduction of a double binding on C 1 -C 2 of the cortisol A ring increases the binding affinity of prednisone/prednisolone more than the cortisol itself for its serum binding proteins, by changing the directions of the steroid molecule, so the ring D and C 21 are oriented towards the pocket of the paratope [65,97] instead of the A ring as in succinate esters.…”
Section: Immediate Reactionsmentioning
confidence: 83%
See 3 more Smart Citations
“…In fact, patients allergic to the GCs of group A (hydrocortisone and methylprednisolone) tolerate the GCs of group C (betamethasone, dexamethasone, paramethasone). Patients with immediatetype reactions to intravenous succinate esters of hydrocortisone and methylprednisolone tolerate prednisolone (a GC of group A) orally, as reported by many authors [23,24,65,66]. This is probably due to the fact that the introduction of a double binding on C 1 -C 2 of the cortisol A ring increases the binding affinity of prednisone/prednisolone more than the cortisol itself for its serum binding proteins, by changing the directions of the steroid molecule, so the ring D and C 21 are oriented towards the pocket of the paratope [65,97] instead of the A ring as in succinate esters.…”
Section: Immediate Reactionsmentioning
confidence: 83%
“…In fact, the tolerability of alternative halogenated GCs, such as betamethasone and dexamethasone, in patients who suffered immediate hypersensitivity reactions to succinate esters of hydrocortisone or methylprednisolone, besides be- ing reported in various cases and numerous reviews [23,24], has been confirmed in two studies [60,67] that evaluated, respectively, 7 and 10 patients with IgE-mediated asthma.…”
Section: Immediate Reactionsmentioning
confidence: 87%
See 2 more Smart Citations
“…Allergic, pseudoallergic, and hypersensitive reactions, although rare, must also remain a consideration, with risk factors including reintroduction of corticosteroids secondary to underlying disease, female gender, and hypersensitivity to acetylsalicylic acid. 178,179 Steroid-induced myopathy is an additional adverse effect particularly problematic in sedentary and female patients, and those patients receiving concomitant neuromuscular blocking agents, aminoglycosides, or propofol. [180][181][182] Etomidate-induced adrenal insufficiency must also be considered in trauma patients who receive this sedative agent during intubation.…”
Section: Adrenal Insufficiencymentioning
confidence: 99%